STRESS IN ORGANIZATIONS - Maria-Elena, GHEORDUNESCU; Laura-Filofteia, PANOIU (Strategii Manageriale)
Taking into account the changes that are currently taking place in our country, it is clear that these changes, which occur in almost all companies, lead to new stress factors for both employees and the organization. Occupational stress is a major problem for employees and managers, but also for the whole society. The issue of stress in organizations has given birth to many debates and studies. It is a common theme that is addressed by managers, employees and consultants from different perspectives. According to a study by the European Agency for Safety and Health at Work, in the European Union, work-related stress is the second work-related health issue after dorsal disorders. It affects 28% of EU employees. The European Parliament is fully involved in addressing issues related to the psychological support of the staff. Preventing work-related stress is one of the objectives set out in the Communique of the European Commission for Employment and Social Affairs regarding their new health and safety at work strategy. Manifestations of stress in organizations are easily observable, being manifested by behaviors such as: difficulties in adapting to the changes required to work or the dramatic drop in labor productivity. Also a double action is met: both the person who passes through the stressful situation and at the organization level on which it is reflected the existence of a stressful environment. This paper aims to address the implications of workplace stress, symptoms of stress in the workplace and strategies to eliminate and prevent stress at work This paper represents an exploratory research based on qualitative methods, being consulted various sources of information: the literature, case studies, media articles, reports of relevant organizations, etc.